A Comparative Study of Embedded and Anesthetized Zebrafish in vivo on Myocardiac Calcium Oscillation and Heart Muscle Contraction - Muntean, Brian; Horvat, Christine; Behler, James; AbouAlaiwi, Wissam; Nauli, Andromeda; Williams, Frederick; Nauli, Surya (Frontiers in Pharmacology, 2010)
The zebrafish (Danio rerio) has been used as a model for studying vertebrate development in the cardiovascular system. In order to monitor heart contraction and cytosolic calcium oscillations, fish were either embedded in methylcellulose or anesthetized with tricaine. Using high-resolution differential interference contrast (DIC) and calcium imaging microscopy, we here show that dopamine and verapamil alter calcium signaling and muscle contraction in anesthetized zebrafish, but not in embedded zebrafish. In anesthetized fish, dopamine increases the amplitude of cytosolic calcium oscillation with a subsequent increase in heart contraction, whereas verapamil decreases the frequency of calcium oscillation and heart rate. Interestingly, verapamil also increases myocardial contraction. Our data further indicate that verapamil can increase myocardial calcium sensitivity in anesthetized fish. Taken together, our data reinforce in vivo cardiac responses to dopamine and verapamil. Furthermore, effects of dopamine and verapamil on myocardial calcium and contraction are greater in anesthetized than embedded fish. We suggest that while the zebrafish is an excellent model for a cardiovascular imaging study, the cardio-pharmacological profiles are very different between anesthetized and embedded fish.